2011
DOI: 10.1007/s10549-010-1330-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in return to work of breast cancer survivors

Abstract: Conclusions:In the Netherlands, the proportion of employed women who fully resumed working after breast cancer within one year of diagnosis has decreased since 2002. These results warrant more epidemiological research to examine the trends in RTW of breast cancer survivors across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 24 publications
2
34
2
3
Order By: Relevance
“…After 1 month from diagnosis 45% of patients stopped work and after 3 to 9 months 55,3% of patients stopped work. In our group of patients, 77,9% of them had full RTW after a median delay of 10,3 months, that is inferior when compared with the delay reported by Roelen et al [1]. Anxiety and depression seem affect employment by decreasing work hours, and increasing absence.…”
Section: Return To Work After Treatment For Breast Cancercontrasting
confidence: 61%
See 2 more Smart Citations
“…After 1 month from diagnosis 45% of patients stopped work and after 3 to 9 months 55,3% of patients stopped work. In our group of patients, 77,9% of them had full RTW after a median delay of 10,3 months, that is inferior when compared with the delay reported by Roelen et al [1]. Anxiety and depression seem affect employment by decreasing work hours, and increasing absence.…”
Section: Return To Work After Treatment For Breast Cancercontrasting
confidence: 61%
“…Also the importance of social support from the workplace in relation to sickness absence in general is well documented [7] and more recently Johnsson et al [8], in their study, clearly demonstrated the importance of social support from the employer and coworkers for the return to work. Work is important for individual's identity and provides also a social connection, however the experience of continuing or returning to work following cancer and related treatment is a largely unknown area of cancer research , so we believe that the report of Roelen et al [1] …”
Section: Return To Work After Treatment For Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][29][30][31]38 To quantify the rehabilitation services used by cancer survivors, cancer registry databases can be linked with those of the structures providing rehabilitation services. For example, a Danish study combined cancer registry and population-based databases to assess hospitalisation for depression as a measure of the psychological burden experienced by cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example a Dutch study used the ArboNed Occupational Health Service register, containing sickness absence data and medical diagnoses for 1 million Dutch wage earners working in 33,000 companies in various economic sectors, to estimate return to work. [23][24][25][26] Cancer registry data were linked to census data in Finland, 27,28 with the Directorate of Taxes database in Norway, 29 and with the Labour Market Research Database in Denmark. 30,31 However, these methods of study cannot be extended to other countries because the occupational databases exploited by these studies do not exist in most other European countries.…”
Section: Indicators On Measures Of Rehabilitation Successmentioning
confidence: 99%